Adherence to statin therapy favours survival of patients with symptomatic peripheral artery disease. Issue 4 (10th December 2019) - Dopheide, Jörn F; Veit, Jonas; Ramadani, Hana; Adam, Luise; Papac, Lucija; Vonbank, Alexander; Kaspar, Mathias; Rastan, Aljoscha; Baumgartner, Iris; Drexel, Heinz
Abstract: Aims : We hypothesized that adherence to statin therapy determines survival in patients with peripheral artery disease (PAD). Methods and results : Single-centre longitudinal observational study with 691 symptomatic PAD patients. Mortality was evaluated over a mean follow-up of 50 ± 26 months. We related statin adherence and low-density lipoprotein cholesterol (LDL-C) target attainment to all-cause mortality. Initially, 73% of our PAD patients were on statins. At follow-up, we observed an increase to 81% ( P  < 0.0001). Statin dosage, normalized to simvastatin 40 mg, increased from 50 to 58 mg/day ( P  < 0.0001), and was paralleled by a mean decrease of LDL-C from 97 to 82 mg/dL ( P  < 0.0001). The proportion of patients receiving a high-intensity statin increased over time from 38% to 62% ( P  < 0.0001). Patients never receiving statins had a significant higher mortality rate (31%) than patients continuously on statins (13%) or having newly received a statin (8%; P  < 0.0001). Moreover, patients on intensified statin medication had a low mortality of 9%. Those who terminated statin medication or reduced statin dosage had a higher mortality (34% and 20%, respectively; P  < 0.0001). Multivariate analysis showed that adherence to or an increase of the statin dosage (both P  = 0.001), as well as a newly prescribed statin therapy ( P  = 0.004) independently predicted reduced mortality. Conclusion : Our data suggest that adherence to statin therapy is associated with reduced mortality in symptomatic PAD patients. A strategy of intensive and sustained statin therapy is recommended.